Urban-rural inequality in lung cancer risk from indoor air pollution: Prolonged indoor time amplifies the risks of solid fuel use - Ruimin Yang; Xinlin Mu; Guilian Wang; Deliang Tang; Bin Wang; Zhiwen Li; Haidong Kan; Nan Lin; Shu Tao (Journal of Environmental Management, 2025)

Green and efficient electrospinning of ethyl cellulose-based nanofibrous membrane for high-performance and antibacterial air filtration - Ruixin Chen; Qibin Wang; Ruimin Shen; Zeqian Gui; Yuhang Yan; Min Tang; Zhiwei Chen; Zungui Shao; Gaofeng Zheng (Carbohydrate Polymers, 2025)

Spatial Heterogeneities of O2O Retail Space in Urban China Under Digital Transformation: Evidence from Guangzhou, China - Zongcai Wei; Weichao Huang; Qijing Tang; Ruimin Xie (Chinese Geographical Science, 2025)

Metal leaching accompanied with natural photo-aging behavior of e-waste plastic derived microplastics in aquatic environment - Jianshuai Zhang; Shuyuan Yu; Zhe Xu; Ruimin Qi; Yihan Chi; Lijuan Wang; Lili Liu; Yuanyuan Tang (Journal of Environmental Sciences, 2025)

Complex release dynamics of microplastic additives: An interplay of additive degradation and microplastic aging - Zhe Xu; Jianshuai Zhang; Ruimin Qi; Qi Liu; Hongmei Cao; Feng Wen; Yixin Liao; Kaimin Shih; Yuanyuan Tang (Journal of Hazardous Materials, 2025)

The ionospheric response during the 2013 stratospheric sudden warming over the East Asia region - Feifei Wang; Ji Tang; Xinjian Shan; Hongbo Zhang; Na Li; Yabin Zhang; Ruimin Jin; Tong Xu (Advances in Space Research, 2024)

Regulatory path for soil microbial communities depends on the type and dose of microplastics - Ruimin Qi; Davey L. Jones; Yuanyuan Tang; Fengxiang Gao; Jiawei Li; Yihan Chi; Changrong Yan (Journal of Hazardous Materials, 2024)

Active and intelligent collagen films containing laccase-catalyzed mulberry extract and pickering emulsion for fish preservation and freshness indicator - Ruimin Ran; Yongming Xiong; Tingting Zheng; Pingping Tang; Yuanzhi Zhang; Changkai Yang; Guoying Li (Food Hydrocolloids, 2024)

Abscisic acid promotes selenium absorption, metabolism and toxicity via stress-related phytohormones regulation in Cyphomandra betacea Sendt. (Solanum betaceum Cav.) - Xun Wang; Wen Lu; Ziming Zhao; Wenhui Hao; Ruimin Du; Zhiyu Li; Zhihui Wang; Xiulan Lv; Jin Wang; Dong Liang; Hui Xia; Yi Tang; et al. (Journal of Hazardous Materials, 2024)

Occurrence and characteristics of microplastics in soils from greenhouse and open-field cultivation using plastic mulch film - Ruimin Qi; Yuanyuan Tang; Davey L. Jones; Wenqing He; Changrong Yan (Science of The Total Environment, 2023)

An injectable, self-healing, and antioxidant collagen- and hyaluronic acid-based hydrogel mediated with gallic acid and dopamine for wound repair - Changkai Yang; Yuanzhi Zhang; Xiaoxia Zhang; Pingping Tang; Tingting Zheng; Ruimin Ran; Guoying Li (Carbohydrate Polymers, 2023)

Antioxidant and antimicrobial collagen films incorporating Pickering emulsions of cinnamon essential oil for pork preservation - Ruimin Ran; Tingting Zheng; Pingping Tang; Yongming Xiong; Changkai Yang; Min Gu; Guoying Li (Food Chemistry, 2023)

Collagen films functionalized with gallic acid in the presence of laccase for beef preservation - Pingping Tang; Tingting Zheng; Ruimin Ran; Yongming Xiong; Guoying Li (Food Packaging and Shelf Life, 2023)

Development of active packaging films based on collagen/gallic acid-grafted chitosan incorporating with ε-polylysine for pork preservation - Tingting Zheng; Pingping Tang; Changkai Yang; Ruimin Ran; Guoying Li (Food Hydrocolloids, 2023)

Antagonistic action of Streptomyces pratensis S10 on Fusarium graminearum and its complete genome sequence - Jing Zhang; Jing Chen; Lifang Hu; Ruimin Jia; Qing Ma; Jiangjiang Tang; Yang Wang (Environmental Microbiology, 2021)
Summary Wheat scab, mainly caused by Fusarium graminearum , can decrease wheat yield and grain quality. Chemical pesticides are currently the main control method but have an inevitable negative consequence on the environment and in food safety. This research studies a promising substitute, Streptomyces pratensis S10, which was isolated from tomato leaf mould and shows a significant inhibition effect on F. graminearum based on antagonism assays. The biocontrol mechanism is studied by enhanced green fluorescent protein labelling, quantitative real‐time PCR, the Doskochilova 8 solvents system test and complete genome sequencing. Strain S10 can colonize in the wheat root, control wheat scab and decrease deoxynivalenol (DON) content. The control effects in vitro, planta and the plot experiments were 92.86%, 68.67% and 40.87% to 86.62%, respectively. S10 decreased DON content by inhibiting the mycelium growth and DON synthesis gene expression. The active substances of the S10 secondary metabolites had a high‐temperature resistance and 29 putative biosynthetic gene clusters in its genome. The S10 control mechanism is multivariate, which shows potential in controlling wheat scab.

Transcriptome analysis of heat stress response genes in potato leaves - Ruimin Tang; Sanjay K. Gupta; Suyan Niu; Xiu-Qing Li; Qing Yang; Guanshui Chen; Wenjiao Zhu; Muhammad Haroon (Molecular Biology Reports, 2020)

Integrated assessment of the environmental and economic effects of “coal-to-gas conversion” project in rural areas of northern China - Yue Li; Xueliang Yuan; Yuzhou Tang; Qingsong Wang; Qiao Ma; Ruimin Mu; Junhua Fu; Jinglan Hong; Jon Kellett; Jian Zuo (Environmental Science and Pollution Research, 2020)

Effects of Earliness on Heat Stress Tolerance in Fifty Potato Cultivars - Guodong Zhang; Ruimin Tang; Suyan Niu; Huaijun Si; Qing Yang; Benoit Bizimungu; Sharon Regan; Xiu-Qing Li (American Journal of Potato Research, 2020)

Environmental and economic impact assessment of the alumina–carbon refractory production in China - Yuzhou Tang; Yifei Shi; Yue Li; Xueliang Yuan; Ruimin Mu; Qingsong Wang; Qiao Ma; Jinglan Hong; Shensong Cao; Jian Zuo; Jon Kellett (Clean Technologies and Environmental Policy, 2019)

Isolation and functional characterization of the SpCBF1 gene from Solanum pinnatisectum - Wenjiao Zhu; Ke Shi; Ruimin Tang; Xiaoying Mu; Jinghui Cai; Min Chen; Xiong You; Qing Yang (Physiology and Molecular Biology of Plants, 2018)

Rapid Screening of Potato Cultivars Tolerant to Nitrogen Deficiency Using a Hydroponic System - Xiaofang Xie; Xiu-Qing Li; Bernie J. Zebarth; Suyan Niu; Ruimin Tang; Helen H. Tai; Benoit Bizimungu; Weiren Wu; Muhammad Haroon (American Journal of Potato Research, 2018)